Prednisone use, disease activity and the occurrence of hyperglycaemia and diabetes in patients with early rheumatoid arthritis: a 10-year subanalysis of the BeSt study - Cornelia F Allaart; Tom W J Huizinga; Sytske Anne Bergstra; Willem Lems; Sjoerd M van der Kooij; Joy Ardjuna van der Pol (RMD Open)
Objectives To assess whether prednisone use and/or disease activity score (DAS) are associated with the development of hyperglycaemia and diabetes in rheumatoid arthritis (RA).Methods We included 504 non-diabetic early RA patients from the BeSt study (Dutch acronym for treatment strategies). Patients were randomised to four DAS-steered treatment arms and followed for 10 years. The associations between DAS and prednisone use with glucose levels and the occurrence of hyperglycaemia over time were assessed with linear and logistic mixed effects regression models. Development of diabetes was analysed with Cox regression. Sensitivity analyses were performed in patients who had a first episode of hyperglycaemia.Results 31 of 504 patients (6.2%) with a mean age of 54 years developed diabetes during follow-up; 11 of these (35%) had received prior treatment with prednisone. Prednisone use was not associated with development of hyperglycaemia or diabetes after correction for multiple testing in main or sensitivity analyses. In the main analyses, DAS was significantly associated with development of diabetes (HR 1.802 per 1 point DAS increase, 95% CI 1.284 to 2.529) but not with glucose levels nor hyperglycaemia. In patients with previous hyperglycaemia, DAS was associated with glucose levels, recurrence of hyperglycaemia and diabetes.Conclusions In non-diabetic early RA patients, the use of prednisone was not associated with developing hyperglycaemia or diabetes. However, high DAS increased the risk of diabetes. Potential risks associated with prednisone use may have been mitigated by its effect on DAS.